Fertilizantes minerais e aminoácidos aplicados via foliar na produtividade, desenvolvimento vegetativo e nutrição do cafeeiro - Costa, Reinaldo Adriano (2009)
The purpose of this work was to evaluate the vegetative development, yield and income, leaves macro and micronutrients content from the Acaiá Cerrado cultivar, trait MG- 1474, cultivated under fertilizers formulations applied over the leaves during the period from 2007 to 2009. The experiment was conducted at Pedra Branca´s Farm, situated at the km 14 by MG265, and has an altitude of 912 m, localized at Uberlândia, in Minas Gerais, Brasil, under Red Oxisol with medium texture. The weather is the type of Aw, with a dry winter and a hot and rainy summer. The experimental delineation used was a randomized block, with three replication and eight treatments, being T1 (Plantin CaB2 + Plantin II), T2 (Plantin CaB2 + Ferty-Mould + Plantin II), T3 (Plantin CaB2 + Ferty- Mould + Plantin II), T4 (Plantin II + Ferty-Mould), T5 (Plantin II), T6 (salt combination), T7 (Plantin CaB2 + Ferty-Mould + Plantin Plus + Plantin II), T8 (control). The planting was done on January 2004, and after three years (coffee plant in formation) there were done the spraying over the leaves. The plots were composed of two rows and eight plant each, space of 0, 8 m between plants and 4, 0 m between rows, having as boarder two plants on each side. Annually, there were measured the yield, coffee plant height, crown and trunk diameter, plagiotrophycal branch length and the number of internodes on the ortotrophycal branch and leaves nutrients content. The coffee leave fertilization did not favored for a higher average plants height, branch diameter, internodes number, and plagiotrophycal branch length on the two seasons evaluated. The use of amino acids on the coffee plant did not contribute for a higher yield and vegetative development, as well as for a higher nutrient concentration on the leaves. The leaves fertilizers Plantin CaB2 + Ferty-Mould + Plantin II, presented higher yields on the two evaluated seasons, although it was no sufficient to differ from control.